Kosovo : a short history - Malcolm, Noel. ([S.l.] : Pan Books, 2002)
By the early-1980s Kosovo had reached a state of permanent crisis and military occupation, and it became the main focus for the revival of Serbian nationalism. This book traces the history of Kosovo, examining the Yugoslavian conflict, and the part played by Western Europe in its destruction. 'This is a profound and important book, essential reading for those who wish to understand either the complex history or the present politics of Yugoslavia.' - Hugh Trevor-Roper, "Sunday Telegraph". 'A dreadnought of a book, all big guns, covering the whole history of Kosovo, with an authority that is often breathtaking and never oppressive.' - Norman Stone, "Sunday Times".
Keywords: Ethnic relations; Kosovo (Republic); Political science; Yugoslav War (1991-1995)